2003
DOI: 10.1536/jhj.44.515
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Impaired Chronotropic Response, Cardiac Output During Exercise, and Exercise Tolerance in Patients with Chronic Heart Failure

Abstract: SUMMARYThe present study was undertaken to investigate the relationship between the extent of impaired chronotropic response and cardiac output during exercise, and exercise tolerance in patients with chronic heart failure. The subjects consisted of 24 patients (mean 60.1 ± 14.0 years) who had mild chronotropic incompetence. Cardiopulmonary exercise testing was performed in all patients, and heart rate (HR), anaerobic threshold (AT), maximum oxygen uptake (peak VO 2 ), slope of the regression line relating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
2
22
1
Order By: Relevance
“…Interestingly, in healthy controls the HR reserve was highly correlated with the increase in plasma norepinephrine but this relationship was uncoupled in HF patients, suggesting diminished sinus node responsiveness in the latter group. This finding is consistent with other lines of evidence, including that from Samejima et al 18 who demonstrated that the ratio of change in HR to change in log of norepinephrine (delta HR/delta log NE), an index of sinoatrial node sympathetic responsiveness, decreased progressively with the severity of HF. Consequently, it appears that at least one mechanism responsible for this derangement has been determined, which will facilitate approaches to address this potential therapeutic ‘target’.…”
supporting
confidence: 92%
“…Interestingly, in healthy controls the HR reserve was highly correlated with the increase in plasma norepinephrine but this relationship was uncoupled in HF patients, suggesting diminished sinus node responsiveness in the latter group. This finding is consistent with other lines of evidence, including that from Samejima et al 18 who demonstrated that the ratio of change in HR to change in log of norepinephrine (delta HR/delta log NE), an index of sinoatrial node sympathetic responsiveness, decreased progressively with the severity of HF. Consequently, it appears that at least one mechanism responsible for this derangement has been determined, which will facilitate approaches to address this potential therapeutic ‘target’.…”
supporting
confidence: 92%
“…24 The clinical sequalae of these autonomic changes include an impaired HR response to exercise (chronotropic incompetence), which may contribute to exercise limitation. 25,26 Indeed, studies have shown that as the severity of systolic heart failure worsens the more common chronotropic incompetence during exercise becomes in patients with CHF. 27 Nevertheless, even in asymptomatic patients with reduced LVEF and LV dilatation poor HR response has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 It is believed that one of the survival benefits conferred by β-blockers in HF is mediated by an increase in both β-receptor density and sensitivity to adrenergic stimulation. 29,30 If β-blockers were indeed the dominant cause of CI in patients with advanced HF, then withdrawal of these agents should result in restoration of the normal chronotropic response to endogenous NE.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Some studies have suggested that abnormal HR response underlies exercise intolerance in HF. 9,12,13 This finding has informed the development of new therapies, such as rate-responsive pacing, with the goal of improving exercise tolerance in this patient population. 14,15 However, in patients with HF who are taking β-blockers, controversy exists about whether CI and exercise intolerance are effects of disease progression alone or whether they also can be attributed to pharmacological β-blockade.…”
Section: Clinical Perspective On P 565mentioning
confidence: 99%